2013
DOI: 10.1002/cem.2577
|View full text |Cite
|
Sign up to set email alerts
|

Chemometrics study of the kinetics of the Griess reaction

Abstract: The kinetics of the Griess reaction in which 3‐nitroaniline acts as a nitrosation agent and 1‐naphtylamine as a coupling reagent was studied by chemometrics methods. The kinetic reaction was investigated under pH 1.0 and 25°C by UV‐vis spectrophotometry. The concentrations of nitrite, 3‐nitroaniline and 1‐naphtylamine were such that a second‐order kinetic reaction took place. Data explorations based on principal component analysis and multivariate curve resolution–alternating least squares were performed to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Interestingly, after adding N -(1-naphthyl)­ethylenediamine dihydrochloride to the reaction solution of m -CDs and NO 2 – , we observed that the mixed solution immediately changed from colorless to magenta, and the absorbance of the magenta dye was positive in proportion to the concentration of NO 2 – , as shown in the inset of Figure D. These data confirmed the diazonium reaction between m -CDs and NO 2 – under 0.1 M H 2 SO 4 and produced diazonium salt. The diazonium salt was an electron-withdrawing group, and the electron cloud of the n-electron lone pair was not coplanar with the π-electron cloud on the benzene ring, and the transition from n to π* was a forbidden process. The probability of an intersystem crossing transition between S 1 and T 1 was large, inducing the fluorescence quenching of m -CDs.…”
Section: Resultssupporting
confidence: 65%
“…Interestingly, after adding N -(1-naphthyl)­ethylenediamine dihydrochloride to the reaction solution of m -CDs and NO 2 – , we observed that the mixed solution immediately changed from colorless to magenta, and the absorbance of the magenta dye was positive in proportion to the concentration of NO 2 – , as shown in the inset of Figure D. These data confirmed the diazonium reaction between m -CDs and NO 2 – under 0.1 M H 2 SO 4 and produced diazonium salt. The diazonium salt was an electron-withdrawing group, and the electron cloud of the n-electron lone pair was not coplanar with the π-electron cloud on the benzene ring, and the transition from n to π* was a forbidden process. The probability of an intersystem crossing transition between S 1 and T 1 was large, inducing the fluorescence quenching of m -CDs.…”
Section: Resultssupporting
confidence: 65%
“…Traditionally, the Griess reagents, SUL and NED, are added sequentially for nitrite analysis simply because the Griess reaction involves several different steps. , Sequential addition allows diazonium to form first before the addition of the NED reagent to elicit the pink color; the t 90% value for the PAD reaction is normally <20 s, and the maximum absorbance is obtained within 4 min at room temperature (Figure , right). However, while using premixed reagents, PAD formation becomes much slower, with a t 90% of >170 s, and the complete reaction may take as long as 20 min.…”
Section: Resultsmentioning
confidence: 99%